2021
DOI: 10.3390/polym13060853
|View full text |Cite
|
Sign up to set email alerts
|

Curing Behaviors, Mechanical and Dynamic Properties of Composites Containing Chloroprene and Butadiene Rubbers Crosslinked with Nano-Iron(III) Oxide

Abstract: This paper discusses the curing behaviors, mechanical and dynamical properties of composites containing chloroprene rubber (CR) and butadiene rubber (BR) reinforced with mineral fillers. The iron(III) oxide nanoparticles were used as a crosslinking agent of the CR/BR blends. The research aimed to evaluate the effectiveness of nano-iron(III) oxide (nano-Fe2O3) as a new crosslinking agent while producing elastomeric materials with good mechanical properties and reduced flammability. The CR/BR (chloroprene rubber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…A characteristic feature of the tested elastomers (especially polychloroprene) is their susceptibility to thermo-cross-linking, which can limit the formation of liquid products during their combustion. The vulcanization of the CR/BR compositions in the presence of nano-sized zinc made the oxygen index (OI) comparable with the parameters determined in such compounds in our previous works [23][24][25][26][28][29][30][31][32], and only slightly higher than the OI value for similar blends cured with micro-sized zinc [32]. The obtained results indicated that the use of nano-zinc as a cross-linking substance for the CR/BR composites led to the formation of flame-retardant products.…”
Section: Flammability and Toxicity Of Unfilled And Filled Cr/br/nzn V...supporting
confidence: 78%
See 2 more Smart Citations
“…A characteristic feature of the tested elastomers (especially polychloroprene) is their susceptibility to thermo-cross-linking, which can limit the formation of liquid products during their combustion. The vulcanization of the CR/BR compositions in the presence of nano-sized zinc made the oxygen index (OI) comparable with the parameters determined in such compounds in our previous works [23][24][25][26][28][29][30][31][32], and only slightly higher than the OI value for similar blends cured with micro-sized zinc [32]. The obtained results indicated that the use of nano-zinc as a cross-linking substance for the CR/BR composites led to the formation of flame-retardant products.…”
Section: Flammability and Toxicity Of Unfilled And Filled Cr/br/nzn V...supporting
confidence: 78%
“…The test was performed according to PN-ISO 4589-2. The oxygen index (OI) was calculated from Formula (7) [23][24][25][26][28][29][30][31][32]:…”
Section: Determination Of Fire Hazard Flammability and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tensile strength testing is by far the most popular method of evaluating filled materials [ 32 , 33 , 34 , 35 , 36 ]. The incorporation of fillers changes the mechanical properties of the prepared vulcanizates.…”
Section: Resultsmentioning
confidence: 99%
“…Organic-inorganic hybrid materials have been widely applied to explore new materials and their specific features. [1][2][3] Generally, inorganic fillers, such as clay, [4][5][6][7] silica particles, [8][9][10] metal nanoparticles, [11][12][13] and polyhedral oligomeric silsesquioxanes, [14][15][16][17][18][19][20] have been used as composite materials when combined with organic polymers. Poly(dimethylsiloxane) (PDMS), an inorganic polymer, has excellent heat resistance, [21][22][23] transparency, 24,25 biocompatibility, 26,27 and gas permeability 28,29 characteristics; however, its mechanical properties are inferior to those of common organic polymers.…”
Section: Introductionmentioning
confidence: 99%